On-the-Job Training and Academic Performance Among High School Students in the Philippines - Samala, Hazel DR.; P. Samala, Jan Eliezer Michael; Goyenechea, Merlinda O. (International Journal of Psychosocial Rehabilitation, 2020)
On-the-job training (OJT) program is one of the most influential programs in higher education and has been an integral part of the educational system in the Philippines specifically in tertiary and senior high school levels but not in the secondary level. This study determined the OJT and academic performances of Filipino high school students in a Laboratory High School in a State University. Descriptive-correlation method was used and results showed that despite being in the secondary level, the students obtained excellent performance rating in their OJT. The students obtained an average rating in their academic performance. However, other factors which affect their class standing such as time conflict between classes and OJT schedule were revealed. Thus, it is recommended to recalibrate the existing OJT policy and guidelines to enable the future students become well-trained and motivated in achieving excellent performances both in the field and academically.